Wage differential in Indonesian manufacturing industries - Bambang Setiaja, (Penerbit Universiti Kebangsaan Malaysia, 2002)
This study ty to examine validity of efficiency wage models in the labor surplus economy. Indonesian manufacturing sector as a core in fact pay higher wages than the outside-informal sector. The rents sharing scheme found lower than that of developed countries, especially shown by smaller elasticity of wages with respect to value added, capital intensity, concentration ratio, foreign ownership, and size. Meanwhile export orientation industry have not positive impact on wages, and female fraction shows quadratic form. The last finding shows increasing part of wages after female workers become majority. Meanwhile, production-non production groups have different wage determinants pattern. The different impact of size, export, and female fraction variables can be concluded as if the industry’s policy results in wage discount, it tends to be allocated by cutting the production worker wages only. It mean that, the wage gap of managerial or white collar group between high and low paying industries tend to narrow